Effect of bisoprolol on central aortic systolic pressure in Chinese hypertensive patients after the initial dose and long-term treatment - Weiwei Zeng; Brian Tomlinson (Biomolecules & Biomedicine, 2022)
We conducted a prospective open-label cohort study with the aim of examining the effects of the highly β1-selective agent bisoprolol on central aortic systolic pressure (CASP) after the first dose and after 6 weeks’ treatment and whether the CASP response could be predicted from the early response. Chinese patients with primary hypertension (BP ≥ 140/90 mmHg) on no therapy or background amlodipine were treated with bisoprolol 2.5 mg daily for 6 weeks. Brachial systolic BP (Br-SBP), resting heart rate (HR) and CASP were determined at baseline, 24h after the first dose, and pre-dose after treatment for 6 weeks using the BPro® device. In 42 patients (age 54 ± 9 years) the mean reductions in CASP and Br-SBP after 6 weeks of treatment were not significantly different from each other at -14.5 ± 12.7 and -15.4 ± 12.9 mmHg (both p<0.01), respectively. Changes in CASP and Br-SBP were highly correlated after the first dose (r = 0.964, p<0.01) and after 6 weeks (r = 0.963, p<0.01) and the reductions in CASP after 6 weeks were also associated with the reduction in CASP after the first dose (r = 0.577, p<0.01). Bisoprolol was shown to effectively reduce CASP and this effect was directly proportional to the reduction in Br-SBP and of a similar magnitude. More favourable CASP responses to long term therapy may be predicted by greater reductions in CASP after the first dose.